2020
DOI: 10.1109/emr.2020.3014280
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Transformation During COVID-19

Abstract: Organizational transformation is an interesting topic in theory and practice. Achieving organizational transformation is seen as a huge challenge for managers as there are many aspects that the organization needs to deal with. During the COVID-19 lockdown, organizations faced an urgent need to radically transform in order to survive. Moreover, the economic and social context of the Mexican economy makes it even more important to understand how organizations can radically transform as, in theory, such a context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Under Covid-19 pandemic most companies in order to survive and ensure their business continuity engaged to a large extent in organizational transformation which involved the measures like retaining the key employees, implementing digital solutions and outsourcing business support functions such as accounting, payroll and IT services to reduce the costs and rely on experts to use the best practices (Robles, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Under Covid-19 pandemic most companies in order to survive and ensure their business continuity engaged to a large extent in organizational transformation which involved the measures like retaining the key employees, implementing digital solutions and outsourcing business support functions such as accounting, payroll and IT services to reduce the costs and rely on experts to use the best practices (Robles, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to remote work and digital delivery of services during Covid-19 pandemic the use of cloud applications increased significantly in sharing data and information between parties (Carungu et al, 2021). Most companies in order to survive and ensure the business continuity engaged in organizational transformation applying measures such as retaining the key employees, implementing digital solutions and outsourcing some business support functions (Robles, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This problem can require institutions to carry out organizational transformation to remain relevant and adapt to these changes. This is as explained by (Haryono et al, 2018) and (Robles, 2020) that the Regional People's Legislative Council as a government organization related to various entities, including the community has the greatest interest for adoption. This organization most of its activities are hearings to discuss various matters.…”
Section: Introductionmentioning
confidence: 96%
“…Crises of enormous magnitudes, such as the COVID-19 pandemic, political instability resulting from national or international conflict and economic downturn inevitably bring change that has the potential for permanence. In the case of COVID-19, Robles (2020), in his study of 21 organizations in Mexico during the first year of the pandemic, found that six organizations experienced minimal change, ten, a medium degree of transformation and five radically transformed. It would be interesting to know if these transformations are enduring.…”
Section: Introductionmentioning
confidence: 99%